2012
DOI: 10.4018/978-1-4666-0182-6
|View full text |Cite
|
Sign up to set email alerts
|

Robots in K-12 Education

Abstract: In this chapter we describe an inquiry based science education (IBSE) theoretical framework applied to robotics activities carried out in European K-12 classrooms during last six years. Interactions between IBSE, problem-based learning, constructivist/constructionist learning theories and technology are discussed. Example activities will show that educational robotics may capitalize on the digital curiosity of young people leading to concrete experiences in STEM content areas and spreading computational thinki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…In previous projects using earlier versions of the curriculum, 17 Overall, the curriculum has worked best in the informal environments. This may be attributed to the amount of time spent on the curriculum during intensive summer camp experiences whereas there is a great range of class time devoted to the curriculum in the formal environment.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…In previous projects using earlier versions of the curriculum, 17 Overall, the curriculum has worked best in the informal environments. This may be attributed to the amount of time spent on the curriculum during intensive summer camp experiences whereas there is a great range of class time devoted to the curriculum in the formal environment.…”
Section: Discussion and Next Stepsmentioning
confidence: 99%
“…In research on previous projects using earlier versions of the curriculum, 62 teacher content knowledge and confidence in teaching the content area were shown to be significant factors in explaining the variance in student post-test scores. That was not the case in this analysis, which indicated that teacher/educator knowledge of the topic was not correlated with student post-test scores for any topic except programming.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Robotics offers an exciting and engaging context for students to learn science and engineering concepts and skills, 33,34,35,36,37,38,39 as well as an educational strategy to increase students' excitement and motivation for STEM areas. 40,41,42,43,44,45 It also offers students an opportunity to practice 21st century skills such as teamwork, problem-solving, and creativity and innovation. 46,47,48,49,50 Robotics has been demonstrated as an effective vehicle to teach STEM concepts at many levels.…”
Section: Instructional Design Principlesmentioning
confidence: 99%
See 1 more Smart Citation